Evaluation of the lymphocyte trafficking drug FTY720 in vaginal tissues. Issue 2 (12th January 2013) - Tsuiki, Ai; Luo, Wei; Henning, Tara; Vishwanathan, Sundaram; Dinh, Chuong; Adams, Debra; Sweeney, Elizabeth; Mitchell, James; Bachman, Shannon; Sharma, Prachi; Powell, Nathaniel; Hendry, Michael; et al.
Abstract: Background: FTY720 is an immunomodulatory agent that reduces lymphocytes in peripheral tissues and circulation. Such agents may be effective as vaginal microbicides for HIV prevention. Systemic or vaginal application of FTY720 may reduce lymphocyte concentrations in genital tissues, reducing HIV target cell numbers. Methods: Five female pigtail macaques received topical vaginal gel FTY720 (n = 2), intravenous (IV) FTY720 (n = 2), or placebo gel (n = 1) in this pilot study. Circulating and mucosal lymphocytes and genital mucosa, cytokines, and tissue histology were analyzed to document topical and IV FTY720 effects. Results: Topical and IV FTY720 appeared to decrease the levels of cervicovaginal IL‐8, IL‐1ra, and genital inflammatory cells. Small sample size precluded statistical analysis. Topical administration had no overt adverse effects. Conclusions: This study introduces FTY720 as an immunomodulatory agent for the vaginal mucosa, compares topical effects to those of IV administration, and provides the basis for future studies involving FTY720 for HIV prevention.